Inhibition of Protein-tyrosine Phosphatase 1B (PTP1B) Mediates Ubiquitination and Degradation of Bcr-Abl Protein - Alvira, Daniel (American Society for Biochemistry and Molecular Biology, 2011)
Chronic myelogenous leukemia (CML) is a myeloproliferative disorder characterized at the molecular level by the expression of Bcr-Abl, a chimeric protein with deregulated tyrosine kinase activity. The protein-tyrosine phosphatase 1B (PTP1B) is up-regulated in Bcr-Abl-expressing cells, suggesting a regulatory link between the two proteins. To investigate the interplay between these two proteins, we inhibited the activity of PTP1B in Bcr-Abl-expressing TonB.210 cells by either pharmacological or siRNA means and examined the effects of such inhibition on Bcr-Abl expression and function. Herein we describe a novel mechanism by which the phosphatase activity of PTP1B is required for Bcr-Abl protein stability. Inhibition of PTP1B elicits tyrosine phosphorylation of Bcr-Abl that triggers the degradation of Bcr-Abl through ubiquitination via the lysosomal pathway. The degradation of Bcr-Abl consequently inhibits tyrosine phosphorylation of Bcr-Abl substrates and the downstream production of intracellular reactive oxygen species. Furthermore, PTP1B inhibition reduces cell viability and the IC(50) of the Bcr-Abl inhibitor imatinib mesylate. Degradation of Bcr-Abl via PTP1B inhibition is also observed in human CML cell lines K562 and LAMA-84. These results suggest that inhibition of PTP1B may be a useful strategy to explore in the development of novel therapeutic agents for the treatment of CML, particularly because host drugs currently used in CML such as imatinib focus on inhibiting the kinase activity of Bcr-Abl.